COMPARISON OF TWO SAMPLING METHODS (CORER AND IN SITU SEDIMENT SIPPER METHODS) FOR THE PORE WATER OF SEDIMENT - Muchtar, Muswerry (Research Center for Oceanography - Indonesian Institute of Sciences (LIPI), 1995)
Effect of two sampling techniques (i.e. corer and sipper samplers) of sediment pore water on measured concentrations of phosphate, nitrate and ammonia was examined. The concentrations of nitrate and ammonia in relation to sediment depth (vertical variations) collected by corer and sipper sampler do not show significant differences, while for phosphate concentrations significant differences occurred. The advantagesÂ Â and disadvantages of both techniques are discussed.